COSO-based longitudinal analysis of public asset management in Indonesia - Puspitarini, Intan; Fuad, Erwansyah (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2026)
Internal control weaknesses in managing Indonesia’s state-owned assets remain a persistent challenge despite regulatory reforms. These weaknesses increase risks of asset loss, inefficiency, and declining public trust. This study examines systemic deficiencies in public asset management using a decade of audit findings (2014-2023) issued by the Audit Board of the Republic of Indonesia. A longitudinal content analysis, guided by the Committee of Sponsoring Organizations (COSO) of the Treadway Commission internal control framework, classifies audit findings across five components: control environment, risk assessment, control activities, information and communication, and monitoring. Results show recurring weaknesses in control activities, including inaccurate registers and incomplete stocktaking, as well as poor system integration, which undermine asset accuracy and safeguarding. These operational gaps persist across audit cycles, indicating that institutional inertia and uneven implementation continue to constrain reform effectiveness, even as ministries frequently receive unqualified audit opinions. The study argues that strengthening public asset governance requires stronger leadership accountability, risk-based asset management, integrated digital systems, and enhanced internal audit capacity. Theoretically, the study extends COSO’s applicability to a longitudinal public sector context; practically, it offers a governance-oriented reform model suited to developing-country administrations.